Crystallization Of Iron Oxide Nanotubes By Anodization And Their Relation To Photocatalytic Properties - Ramli, Norahasyima (Universiti Sains Malaysia, 2018)
Cr(VI) is heavy metal of high toxicity and has been classified as human carcinogen. Cr(VI) enters into environment from sources such as manufacturing industries of leather and tanning alloys and steel, rubber and more importantly textile industries which utilizes Cr(VI) as pigments and dyes. This study is on the applicability of nanostructured porous iron oxide for the removal of Cr(VI) from aqueous solution. The nanostructured iron oxide anodic films were synthesized by direct anodic oxidation technique of carbon steel and then annealed for crystallization of iron oxide. After annealing, α-Fe2O3 formed was characterized by Field Emission Scanning Electron Microscope (FESEM) and X-Ray Diffraction (XRD) for morphologies and phases studies respectively. The parameters experimented were anodization time, effect of voltage and effect of percentage volume of H2O in ethylene glycol used in electrolyte. A mixture of nanoporous, nanosheet and nanowires was observed from these experiments. The nanosheets formed as interconnected nanosheets arrays cell with cell width varies from 26.5 nm to 66.2 nm. Nanoporous structure were formed at 10 minutes anodization time, with 3 ml H2O and 50 V. Nanosheets with mixtures of nanowire were formed. Nanoporous and interconnected nanosheets arrays of iron oxide were used as photocatalysts to reduce Cr(VI) under sunlight. The reduction percentage of Cr(VI) at pH 2 was the fastest after one hour of exposure to sunlight.